(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Prevention is always better than cure especially in diseases such as Type 2 DM which is fast gaining the status of a potential epidemic in India with more than 62 million diabetic individuals currently diagnosed with the disease. The disease Madhumeha can be correlated with Type 2 DM. The disease is characterized by metabolic abnormalities and long term complications involving the eyes, kidneys, nerves and blood vessels. Madhumeha being an Anushangi vyadhi will make the person suffer for life time. Complications are further more difficult to treat. Hence it is always recommended in Ayurvedic classics to prevent the manifestation of diseases as much as possible and also to prevent the Upadravas if Madhumeha is already manifested. A good and proper diet in disease is worth a hundred medicines and no amount of medication can do well to a patient who does not follow a strict regimen of diet. Pathya ahara is the first and foremost step while considering the prevention of Madhumeha. Another factor which has important role in the disease manifestation is improper Vihara which can be considered for increased urbanisation, high prevalence of obesity, sedentary lifestyles and stress. Healthy life style has a key role in preventing Madhumeha and also to ease the life with Madhumeha by delaying the complications. Hence the present study is aimed at collecting and compiling various preventive measures which are explained by our Ayurvedic Acharyas to prevent Madhumeha and its complications.